Peningkatan Motivasi Belajar Muatan IPA Melalui Penggunaan Media Realia pada Siswa Kelas V SD Negeri Kedai Runding - Faizin Faizin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The purpose of this study is to analyze the improvement of learning motivation for science subjects of fifth grade students at SDN Kedai Runding by using realia media. The research was conducted at SDN Kedai Runding, Kec. Kluet Selatan, Kab. Aceh Selatan. The research subjects were 10 fifth grade students in the first semester of the 2020/2021 academic year. The research method used was a classroom action research using the Kemmis and Mc Taggart cycle model with four stages in each cycle: planning, action implementation, observation, and reflection. Data collection techniques were carried out by filling out questionnaires and conducting interviews, as well as collecting data using documentation/photos taken during the learning process. The research results show that the data obtained from the learning process using realia media in cycle I was 83.08%, and cycle II was 93.75%. The average student motivation score in cycle I was 84.26, and cycle II was 101.28, with a theoretical score ranging from 30-120. Thus, learning by using realia media can improve students’ learning motivation. The implication of this research is that the use of realia media in learning science subjects can be an alternative to foster or improve students’ learning motivation in fifth grade at SDN Kedai Runding.